1996
DOI: 10.1152/ajplung.1996.270.4.l487
|View full text |Cite
|
Sign up to set email alerts
|

Salt and water transport across alveolar and distal airway epithelia in the adult lung

Abstract: Substantial progress has been made in understanding the role of the distal airway and alveolar epithelial barriers in regulating lung fluid balance. Molecular, cellular, and whole animal studies have demonstrated that reabsorption of fluid from the distal air spaces of the lung is driven by active sodium transport. Several different in vivo, in situ, and isolated lung preparations have been used to study the mechanisms that regulate fluid transport in the normal and injured lung. Catecholamine-dependent and -i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
273
2
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(284 citation statements)
references
References 57 publications
8
273
2
1
Order By: Relevance
“…Pulmonary tissues develop a large capacity for fluid absorption in the perinatal state and provide humidification of the airways and airway secretions (see Ref. 41 for review). To accomplish this, complex developmental expression patterns have evolved (42) with highly specific distribution patterns (32): AQP1 in peribronchiolar capillary endothelium; AQP3 in basal cells of airway epithelium; AQP4 in tall columnar cells; AQP5 in the apical membrane of type I alveolar pneumocytes and salivary acini.…”
Section: Multiple Aquaporins In Complex Tissuesmentioning
confidence: 99%
“…Pulmonary tissues develop a large capacity for fluid absorption in the perinatal state and provide humidification of the airways and airway secretions (see Ref. 41 for review). To accomplish this, complex developmental expression patterns have evolved (42) with highly specific distribution patterns (32): AQP1 in peribronchiolar capillary endothelium; AQP3 in basal cells of airway epithelium; AQP4 in tall columnar cells; AQP5 in the apical membrane of type I alveolar pneumocytes and salivary acini.…”
Section: Multiple Aquaporins In Complex Tissuesmentioning
confidence: 99%
“…Experimental lung preparations have measured salt and water transport across alveolar and distal airway epithelia. It is generally accepted that the net balance between electrolyte absorption and secretion controls the movement of fluid by osmotic pressure (Boucher, 1994a;Matthay et al, 1996). A primary motion force for the transport of sodium seems to be the sodium/potassium-ATPase (sensitive to oubain), located on the basolateral membrane ( Figure 2).…”
Section: European Journal Of Clinical Nutritionmentioning
confidence: 99%
“…Water can travel through transcellular channels known as aquaporins. However, studies using specific aquaporin-null mice have demonstrated that these channels do not have significant roles in alveolar fluid absorption despite their importance in osmotically driven water movement across epithelial and endothelial cell barriers in the lung [10][11][12][13][14][15]. Cl − is secreted into the alveolar space via the cystic fibrosis transmembrane regulator (CFTR) [16]; this receptor also plays a role in cAMP-mediated fluid transport [17,18].…”
mentioning
confidence: 99%